2019
DOI: 10.1002/cam4.2180
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic disparities in a state‐wide registry of patients with pancreatic cancer and an exploratory investigation of cancer cachexia as a contributor to observed inequities

Abstract: Pancreatic cancer (PC) is characterized by racial/ethnic disparities and the debilitating muscle‐wasting condition, cancer cachexia. Florida ranks second in the number of PC deaths and has a large and understudied minority population. We examined the primary hypothesis that PC incidence and mortality rates may be highest among Black Floridians and the secondary hypothesis that biological correlates of cancer cachexia may underlie disparities. PC incidence and mortality rates were estimated by race/ethnicity, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 48 publications
0
17
0
1
Order By: Relevance
“…In addition, the obesity rates amongst children In Canada are lower than those in USA . This is relevant as ethnicity and obesity have been shown to impact tPMA muscle mass values . The tPMA values derived using our Toronto cohort represent a more diverse population, and we propose to be potentially more broadly generalizable.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, the obesity rates amongst children In Canada are lower than those in USA . This is relevant as ethnicity and obesity have been shown to impact tPMA muscle mass values . The tPMA values derived using our Toronto cohort represent a more diverse population, and we propose to be potentially more broadly generalizable.…”
Section: Discussionmentioning
confidence: 96%
“…AA/Bs have both a higher incidence [269][270][271][272][273] and mortality rate 270,271,[273][274][275] compared with NHWs as well as other populations, which has been documented for both younger and older adults (<50 years vs. >50 years) across all USA states other than Hawaii. 174,271,272 Nearly all racial/ethnic groups showed a steady increase in incidence over a 27-year period from 1988 to 2015, with AI/ANs (who had the lowest incidence of all race/ethnicity groups) showing the greatest increase over time and AA/Bs showing stable incidence rates.…”
Section: Disparities In Pancreatic Cancermentioning
confidence: 93%
“…In 2020, 3570 (7.9%) of the 45,300 cancer-related deaths among Floridians will be due to PaCa and occur mainly in NHW, AA, and H/L [ 1 ], yet PaCa disparities research is limited in Florida’s diverse population. We used Florida Cancer Data System (FCDS) Registry data [ 15 ] to estimate age-adjusted PaCa incidence and mortality rates and found that AA had the highest incidence and mortality rates across genders, mirroring national disparities [ 16 ].…”
Section: Introductionmentioning
confidence: 99%